A Regional Stable Carbon Isotope Dendro-Climatology from the South African Summer Rainfall Area - Woodborne, Stephan (PLoS One, 2016)
Carbon isotope analysis of four baobab (Adansonia digitata L.) trees from the Pafuri region of South Africa yielded a 1000-year proxy rainfall record. The Pafuri record age model was based on 17 radiocarbon dates, cross correlation of the climate record, and ring structures that were presumed to be annual for two of the trees. Here we present the analysis of five additional baobabs from the Mapungubwe region, approximately 200km west of Pafuri. The Mapungubwe chronology demonstrates that ring structures are not necessarily annually formed, and accordingly the Pafuri chronology is revised. Changes in intrinsic water-use efficiency indicate an active response by the trees to elevated atmospheric CO(2), but this has little effect on the environmental signal. The revised Pafuri record, and the new Mapungubwe record correlate significantly with local rainfall. Both records confirm that the Medieval Warm Period was substantially wetter than present, and the Little Ice Age was the driest period in the last 1000 years. Although Mapungubwe is generally drier than Pafuri, both regions experience elevated rainfall peaking between AD 1570 and AD 1620 after which dry conditions persist in the Mapungubwe area until about AD 1840. Differences between the two records correlate with Agulhas Current sea-surface temperature variations suggesting east/west displacement of the temperate tropical trough system as an underlying mechanism. The Pafuri and Mapungubwe records are combined to provide a regional climate proxy record for the northern summer rainfall area of southern Africa.